2019
DOI: 10.1016/j.biosystemseng.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Computational approach to evaluating the strength of eggs: Implications for laying in organic egg production

Abstract: With the aim of characterizing the different stress patterns in several egg types and evaluate the resistivity of the eggshell while impacting in free fall, experimental tests and computational simulations have been performed on eggs of the species Gallus gallus (domestic hen), Struthio camelus (ostrich), and Testudo sp. (tortoise). The different types of failure were determined for each taxa and stress distribution maps were recorded and correlated between experimental results and computational simulations us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…On the basis of this approach, the Hügelschäffer's model was selected as an equation that completely meets the basic principles and requirements for a comprehensive egg shape description. Using the exact description of the geometric shape of the eggs, the principles of a common engineering method known as Finite Element Analysis (FEA) have been developed and widely used to study the strength properties of the shell (Coucke et al, 1998;Nedomová et al, 2009;Perianu et al, 2010;Sellés et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of this approach, the Hügelschäffer's model was selected as an equation that completely meets the basic principles and requirements for a comprehensive egg shape description. Using the exact description of the geometric shape of the eggs, the principles of a common engineering method known as Finite Element Analysis (FEA) have been developed and widely used to study the strength properties of the shell (Coucke et al, 1998;Nedomová et al, 2009;Perianu et al, 2010;Sellés et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, mechanical strength of eggshell is an important factor for the reproductive biology of every oviparous amniote. Experimental compression or simulation studies have shown that eggshell thickness has a positive correlation with the strength of eggshells ( Ar et al, 1979 ; Hahn et al, 2017 ; Juang et al, 2017 ; López et al, 2021 ), and this relationship may even provide a way to infer contact incubation in Palaeognathae (including extinct taxa; Huynen et al, 2010 ; Yen et al, 2021 ) as well as laying process of Palaeognathae ( Sellés et al, 2019 ). However, López et al, 2021 showed that microstructures, which was usually not considered in earlier studies such as finite element method, of avian eggshell can further contribute to the strength of the eggshells.…”
Section: Discussionmentioning
confidence: 99%
“…Perianu et al (2010) simulated both the dynamic characteristics of eggshell and the force of the fluid inside eggshell. Sellés et al (2019) took advantages of finite element to describe the different stress patterns in several egg types, and analysed the stress on the eggshell in free fall impact. Fabbri et al (2011) determined the amount of CO 2 diffusion in various egg parts such as thin and thick albumen, and yolk by using the finite element model.…”
Section: Introductionmentioning
confidence: 99%